1970
DOI: 10.5755/j01.eee.109.3.181
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Feedback and Emotion Recognition in Computer based Speech Therapy System

Abstract: In this paper we present two appropriate ways for the Computer Based Speech Therapy (CBST) improvement. Real-time quality feedback in free environments and emotion recognition could produce a better similarity between human and artificial speech therapist. Using these extended approaches, a CBST system can become a better speech therapist assistant and that is why we intend to implement these technology improvements on our CBST system - Logomon. Ill. 3, bibl. 15 (in English; abstracts in English and Lithuanian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In light of the present data, it has been revealed that emotion recognition ability may be associated with responsive behaviors against the pandemic. In both healthy individuals and individuals with mental illnesses, efforts to increase emotion recognition ability (Greenberg, 2004;Machado et al, 1999;Schipor et al, 2011) can promote to take immediate precautions with enhancing the risk perception against the outbreak. Further research regarding the role of psychiatric disorders would shed light on this field.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the present data, it has been revealed that emotion recognition ability may be associated with responsive behaviors against the pandemic. In both healthy individuals and individuals with mental illnesses, efforts to increase emotion recognition ability (Greenberg, 2004;Machado et al, 1999;Schipor et al, 2011) can promote to take immediate precautions with enhancing the risk perception against the outbreak. Further research regarding the role of psychiatric disorders would shed light on this field.…”
Section: Discussionmentioning
confidence: 99%
“…between an uttered word and a dictionary) and a good recognition rate requires a good quality of pronunciation. In the second case, the next user' utterance is indicated by the system and a similarity measure between received and expected speech sequence is calculated [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…software and hardware improvements). However, although often neglected, some psychological aspects of interaction (Schipor & al., 2011) such as attitude and selfefficacy could also lead to an increasing in performance by offering the motivational background for learning and adaptation to this new technology. In this paper we investigate the attitude and the self-efficacy of subjects with motor impairments and able-bodied people in relation with touchscreens.…”
Section: Introductionmentioning
confidence: 99%